An investigation into the impact of the COVID-19 pandemic upon golfers` strength and conditioning and golf practice - Langdown, B. L.; Ehlert, A. (International Journal of Sports Science & Coaching, 2023)
As the spread of the novel coronavirus disease 2019 increased, governments across the world introduced various restrictions to reduce infections. Stay-at-home orders and lockdowns of golf courses (for 5.08 ± 2.79 months) and strength and conditioning facilities (for 6.78 ± 3.80 months) meant that golfers had to quickly adapt their practice and training. This mixed-methods study surveyed amateur and professional golfers (n = 107), to examine the applied impact of the pandemic on their strength and conditioning, golf practice, tournament engagement, levels of stress and motivation and the impact upon diet and sleep. Results indicate reduced practice frequency and duration across various aspects of golf, as well as reduced tournament engagement. The most commonly cited limiting factors for tournament engagement were a lack of practice time (28.8%) and travel restrictions (52.5%). In general, golfers were motivated to train, with session frequency remaining consistent with pre-pandemic levels. However, golfers suffered from significantly higher levels of stress (p < .001), disturbed sleep (p = .015) and perceptions of less physical gains compared to previous years. While online support has been accessed by 53.8% of golfers, the cited lack of facilities/equipment by 71.9% raises concerns over detraining and injury risks on return to sport. Coaches are urged to monitor athlete self-report measures to manage and optimise interventions, especially in similar situations where maintaining progressive overload is challenging. Strength and conditioning and golf coaches can use this study to review their applied practices, consider benefits/limitations to online coaching and to modify future interventions.